Cutaneous vasculopathy in microscopic colitis: the role of gut-derived endothelial toxins - Jackson, Travis; Gonzalez, Karen; Orestes, Guang; Benitez, Carolina M.; Hassan, Muhammad; Daly, Paige O’Brien; Ayoub, Reem; Fadel, Lynn (International Journal of Research in Medical Sciences, 2025)
Microscopic colitis (MC) is a chronic inflammatory bowel disorder marked by persistent diarrhea and colonic mucosal inflammation. Emerging evidence suggests systemic manifestations, including cutaneous vasculopathy such as livedo reticularis and leukocytoclastic vasculitis, potentially driven by gut-derived endothelial toxins. However, the mechanisms linking MC to microvascular disorders remain poorly understood. This review examines the interplay between MC, gut dysbiosis, and systemic endothelial dysfunction, emphasizing the role of gut-derived toxins like lipopolysaccharides and microbial metabolites in vascular injury. A comprehensive literature search was conducted across PubMed, EMBASE, and Web of Science using predefined terms. Studies were appraised with standardized quality tools, and findings were categorized into endothelial toxin profiles, mechanisms of vascular injury, and clinical correlations. Emphasis was placed on studies using advanced techniques, such as metabolomics for toxin analysis, histopathology for vasculitis lesions, and imaging for vascular assessment. Evidence highlights a potential link between gut-derived toxins and systemic vascular effects in MC, though causality remains unproven. Variability in toxin profiles among MC patients and their correlation with cutaneous manifestations were noted. Key knowledge gaps include mechanisms of endothelial dysfunction, variability in toxin-mediated vascular injury, and lack of standardized diagnostic criteria for MC-associated vasculopathy. Further longitudinal and mechanistic studies are needed. Clarifying the role of endothelial toxins in MC-associated vasculopathy could lead to novel diagnostic biomarkers, therapeutic targets, and improved outcomes for patients with MC and its systemic vascular complications.